Tuning nitrogen species to control the charge carrier concentration in highly doped graphene. (7th January 2016) - Scardamaglia, Mattia; Struzzi, Claudia; Osella, Silvio; Reckinger, Nicolas; Colomer, Jean-François; Petaccia, Luca; Snyders, Rony; Beljonne, David; Bittencourt, Carla
Abstract: Highly nitrogen-doped graphene on copper has been obtained by post-synthesis low-energy ion implantation. Core level and angle resolved photoemission spectroscopies are correlated to link the actual charge carrier doping to the different nitrogen species implanted in the nanostructure. Indeed, we exploit the possibility of controlling the graphitic/pyridinic ratio through thermal heating to tune the charge carrier density; this implicates Dirac cone shifts that are directly correlated to the different doping contribution of the nitrogen species. Supported by density functional theory calculations, we identify graphitic nitrogen as being responsible for n-doping when the amount of counterbalancing pyridinic nitrogen species is reduced upon thermal heating.